The Utilization of GoFood as an Effort to Enhance the Businesses of MSME Actors - Bulloh, Khabib Kitab; Imran, Juani; Idris, Muhamad Syawal; Ismail, Fatmawati; , Syafruddin, , Syafruddin; Amriani, Nur Wardah Desi; Rahman, Shinta Abdul (Fakultas Ekonomi dan Bisnis Islam Universitas Al- Hikmah Indonesia - Jurnal Ekonomi Pengabdian Masyarakat, 2024)
GoFood is a technology-based food delivery service developed by Gojek, one of the largest technology companies in Southeast Asia. This platform utilizes mobile application technology to connect customers with restaurants and driver partners in an integrated ecosystem. GoFood uses advanced algorithms to recommend menus, optimize delivery routes, and monitor service quality in real-time. This technology not only increases user comfort, but also opens up new business opportunities for small and medium enterprise (SME) partners in the culinary industry. In addition, innovative features such as order personalization and digital payments via GoPay provide a more efficient user experience. In this research, the methods we apply include participatory methods and action methods (action research). This research discusses the positive impact of adopting GoFood technology on operational efficiency, increasing restaurant partner income, and ease of access for consumers, as well as identifying challenges that still need to be overcome. ry services